(untitled) (Development Service Industry Management, 2024)
The article examines the main trends and problems related to the policy of sustainable development and corporate governance practices around the world. It is worth noting that the implementation of sustainable development involves the complexity of articulating many dimensions (economic, social, environmental, cultural and political) at different levels (International, national, local) in an inter-institutional manner and under the influence of various entities (the state, companies, multilateral organizations) that have asymmetric positions of power. All this coordination involves serious difficulties in the management process. Sustainable development, according to the UN approach and political ecology, includes environmental issues, and recognizes that natural resources are limited and there should be restrictions on their use to prevent their depletion, since it recognizes that nature is indispensable for maintaining life (Environmental Services, production of goods and services, etc.). In addition, due to the relationship that exists between the dimensions of sustainable development (economic, social, cultural, environmental and Political), any decision made in terms of environmental management affects socio-economic, cultural and political aspects. In turn, these decisions are also influenced by cultural and socio-economic aspects, since they are part of the political process. That is, in both approaches, the goal of sustainable development is to achieve inclusive development, which also includes environmental issues. The conducted research is the result of scientific mapping, supported by various sources, the study of the relationship that exists between publications and authors with the topic of sustainability and corporate governance. Over time, adopting a flexible culture to respond to new changes in the environment and implementing sustainable development processes in organizations has become a very important goal for them, as both processes are aimed at reducing the negative impact of social, environmental and economic situations. Taking these approaches into account, the concept of governance becomes important as a crucial and defining tool in the process of Sustainable Development, which mainly leads to the integration of stakeholders to achieve common goals.